Review of handover mechanisms to support triple play in mobile WiMAX - Ben-Mubarak, Mohammed Awadh; Mohd Ali, Borhanuddin; Noordin, Nor Kamariah; Ismail, Alyani; Ng, Chee Kyun (Institution of Electronics and Telecommunication Engineers, 2009)
Handover (HO) mechanism is one of the critical operations in mobile WiMAX. It takes place when a mobile station (MS) moves from a serving base station (BS) to another BS. However, the HO latency in mobile WiMAX is still an issue that may affect continuity of real-time application sessions such as Voice over Internet Protocol (VoIP). This paper presents performance comparison of some HO mechanisms for real-time applications in mobile WiMAX, including HO, cross-layer HO, pre-coordination HO, passport HO mechanisms and fast intra-network and cross-layer HO (FINCH). Each one of these mechanisms reduces HO latency, especially during downlink traffic; however, they still produce insufficient HO latency during uplink traffic. Except for FINCH, they do not consider the scenario of HO between BSs that belong to different access service network-gateways (ASN-GWs) or to different connectivity service networks (CSNs); these two cases cause extra layer 3 (L3) HO latency.